2019
DOI: 10.1177/1049909119829047
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional Collaboration Between a Multidisciplinary Palliative Care Team and the Team Pharmacist on Pain Management

Abstract: The purpose of the study was to evaluate the impact on pain management by multidisciplinary palliative care team (mPCT) and the team pharmacist. Methods: Patients who were admitted to palliative care unit (PCU) for at least 7 days between April 2014 and December 2015 were included. The mPCT consisted of a physician, a pharmacist, nurses, and non-clinical support staff. The team was on charge of pain management of patients who were admitted to PCU. Pain intensity was assessed at 3 time points in each patient; 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Studies conducted globally have confirmed the benefit of the integration of the OPT as part the MHT within a variety of settings in improving overall patient care. 2252…”
Section: Contributions To Patient Carementioning
confidence: 99%
“…Studies conducted globally have confirmed the benefit of the integration of the OPT as part the MHT within a variety of settings in improving overall patient care. 2252…”
Section: Contributions To Patient Carementioning
confidence: 99%
“…Secondary degrees were included for analysis for the members of the PC interdisciplinary team (physician/licensed independent practitioners [LIPs], nursing, social work, chaplain, therapy, pharmacy). 17,18…”
Section: Resultsmentioning
confidence: 99%
“…Secondary degrees were included for analysis for the members of the PC interdisciplinary team (physician/licensed independent practitioners [LIPs], nursing, social work, chaplain, therapy, pharmacy). 17,18 The primary professional degree was used for the final analysis in the following groupings: MD or equivalent ( The total number of studies for which the first authors' degree was available was 4875. All interdisciplinary degrees were represented in the first authorship except RT and SLP.…”
Section: Professional Degree Of the Authormentioning
confidence: 99%
“…They are also the principal investigators of the associated research studies. The economic and humanistic values of oncology pharmacy services have been well described [2][3][4][5][6][7][19][20][21][22] and the diagnostic value of the pharmacists' services in precision medicine with regard to training and implementation initiatives may be better evaluated.…”
Section: Discussionmentioning
confidence: 99%